Comparison of the Efficiency of Lepidium sativum, Ficus carica, and Punica granatum Methanolic Extracts in Relieving Hyperglycemia and Hyperlipidemia of Streptozotocin-Induced Diabetic Rats - Shimaa Ramadan; Amany Mohamed Hegab; Yahya S. Al-Awthan; Mohammed Ali Al-Duais; Ahmed A. Tayel; Mahmoud A. Al-Saman (Journal of Diabetes Research)
Background. Diabetes mellitus (DM) is a metabolic disorder characterized by high blood glucose levels that occurs either due to insufficient insulin production or mounting resistance to its action. The purpose of this study was to investigate if methanolic extracts of Lepidium sativum seeds, Ficus carica, and Punica granatum leaves had any effect on blood sugar levels in normal and streptozotocin (STZ) diabetic rats, as well as to explore the most effective extract. Method. Healthy male albino rats weighing 185-266 g were divided into nine groups of eight rats each: normal control, diabetic control, diabetic rats with dietary supplements of L. sativum, F. carica, and P. granatum methanolic extracts, and diabetics treated with insulin. All of the rats were fed on ordinary diet with nutritional pellets and were given water ad libitum. To induce diabetes, all animals were administered with STZ intraperitoneal injection at a dose of 60 mg/kg body weight. For five weeks, the crude plant extracts were given orally to various groups of rats at doses of one hundred and two hundred mg/kg body weight. After that, animal groups were sacrificed and blood samples were taken. Results. Phytochemical analysis revealed that the highest amounts of polyphenolic compounds were present in L. sativum seeds and P. granatum leaves, while leaves of F. carica showed the highest amounts of alkaloid and flavonoid content compared to other extracts. Oral administration of F. carica and L. sativum extracts at the dosage of 100 and 200 mg/kg significantly reduced glucose, lipid profile, kidney, and liver enzyme levels. A significant increase in HbAlc levels was also observed with L. sativum extract at a dose of 200 mg/kg compared to diabetic controls. Mellitus rats supplemented with 100 and 200 mg/kg methanolic extracts of P. granatum had higher serum triglycerides and lower serum low-density lipoprotein cholesterol (LDL-C) than normal control rats. F. carica extract is more effective than L. sativum and P. granatum extracts in the prevention and control of type 2 diabetes mellitus (T2DM) and its consequences.